Prospects from exiting the economic models of 1970ies for Ukraine’s post-war economy - Filiak , M.S. (Global Prosperity, 2023)
The article examines the current economic situation in Ukraine. It highlights the need to move away from the economic models of the 1970s and instead adopt modern management practices. The article emphasizes the importance of investing in innovation and technology to boost economic growth. It also discusses the impact of globalization on Ukraine’s economy and the need for the country to find its place in the global market. The article highlights the importance of long-term planning in achieving economic stability and growth. Specifically, the article analyzes the economic situation in Ukraine in the mid-2010s and the effects of the country’s exit from the economic models of the 1970s. The article discusses the shift towards quality over quantity, the decline in entrepreneurship, the tightening of markets, the importance of global management systems, and the trend towards longer-term planning. The article argues that these changes have implications for Ukraine’s economy after 2022, including the need for a shift towards more innovative and sustainable economic models, increased investment in human capital, and the adoption of more strategic and long-term planning approaches. The article concludes that by embracing these changes, Ukraine can position itself for greater economic prosperity and growth in the years ahead.